Health policy issues : an economic perspective - Feldstein, Paul J. (Health Administration Press, a division of the Foundation of the American College of Healthcare Executives, 2019)
One of the best ways to understand healthcare, in all its complexity, is from an economic perspective - that is, from the perspective of all involved parties. The author describes the forces that press for change in healthcare and explains why the US health system has evolved to its current state. This book's issue-oriented chapters cover various aspects of the US health system, including cost of medical care, health insurance, Medicare and Medicaid, physician and nursing shortages, medical school admittance, malpractice reform prescription drugs, and more. Throughout, the book integrates information about the most significant health policy enacted in many years - the Affordable Care Act (ACA). Discussion questions, key points, and further readings round out every chapter. Thoroughly revised and updated with data and research findings, this seventh edition includes expanded content on the Medicare Access and CHIP Reauthorization Act, physician malpractice reform, employee health benefits, generic drug shortages, political versus economic markets, and much more. -- Publisher's description.